How to create a cultural species: Evaluating three proposals. (17th February 2022) - Nichols, Ryan; Moll, Henrike; Mackey, Jacob L
ABSTRACT: This paper summarizes, contrasts, and reviews recent accounts of cultural evolution in our species offered by Cecilia Heyes in Cognitive Gadgets, Kevin Laland in Darwin's Unfinished Symphony, and Michael Tomasello in Becoming Human . Our critical discussion focuses on the authors' accounts of social learning, and the relationship each hypothesizes between cultural evolutionary and biological evolutionary processes. We find that both Laland and Tomasello seek to explain cultural evolution in humans as reliant upon processes of joint attention and shared intentionality (the development of which is largely the focus of Tomasello's book). Heyes' account of social learning, in which no particular role is assigned to human intersubjectivity and the same basic associative learning mechanisms of nonsocial learning are also invoked to explain social learning, stands apart. As to the relation of cultural and biological evolution, Laland offers readers a thorough account of the two with detailed analyses of social learning across various non-primate species, and uniquely, among these authors, attends to the influence of genes on social learning. For his part, Tomasello provides readers with a richly detailed experimental accounting of human-unique forms of social learning using Great Apes as points of contrast.